2021
DOI: 10.3389/fphar.2021.663088
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Toxicities Associated With Immune Checkpoint Inhibitors: A Pharmacovigilance Analysis of the FDA Adverse Event Reporting System (FAERS) Database

Abstract: Introdution: Immune checkpoint inhibitors (ICIs) have significantly improved clinical outcomes for a wide range of cancers but can also lead to serious or fatal immune-related adverse events (irAEs). Although ICI-related pericardial toxicities have been reported, the clinical features are not well characterized in real-world studies.Objective: To characterize the main features of ICI-related pericardial toxicities and identify factors associated with death.Methods: Data from January 1, 2011 to March 31, 2020 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
6
23
0
Order By: Relevance
“…In addition, dual ICI treatments were detected with pharmacovigilance signals of cardiac arrhythmias, myocardial disorders and decreased and nonspecific blood pressure disorders and shock compared with monotherapy. There was no increased risk of pericardial toxicity with combination therapy relative to monotherapy, which was consistent with previous study 23 . Studies have shown that dual ICI therapies (e.g., a CTLA‐4 inhibitor combined with a PD‐1 inhibitor) lead to higher risk of myocarditis, as well as worse outcomes 24,25 …”
Section: Discussionsupporting
confidence: 88%
“…In addition, dual ICI treatments were detected with pharmacovigilance signals of cardiac arrhythmias, myocardial disorders and decreased and nonspecific blood pressure disorders and shock compared with monotherapy. There was no increased risk of pericardial toxicity with combination therapy relative to monotherapy, which was consistent with previous study 23 . Studies have shown that dual ICI therapies (e.g., a CTLA‐4 inhibitor combined with a PD‐1 inhibitor) lead to higher risk of myocarditis, as well as worse outcomes 24,25 …”
Section: Discussionsupporting
confidence: 88%
“…professionals ( Sakaeda et al, 2013 ). The analysis of the FAERS database has been exploited in pharmacovigilance for drug safety assessments, not only to detect drug-AE associations unidentified in pre-market clinical trials, but also protect patients from potential harms ( Chen et al, 2021 ; Eugene et al, 2021 ; Ma et al, 2021 ). It is worth noting that whether a drug is the causative agent of an AE occurring during its use, is something that can only be accurately judged through a rigorous causality assessment by healthcare professionals, while non-healthcare professional reports on their own appear to increase the risk of erroneous information ( Andreaggi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FAERS database, established for national post-market surveillance for drug safety, is a spontaneous reporting system for healthcare professionals, consumers, and drug manufacturers ( Sakaeda et al, 2013 ). As FAERS case reports have been increasing annually, the database is largely used to identify novel drug-associated AEs not previously observed in clinical trials ( Chen et al, 2021 ; Eugene et al, 2021 ; Ma et al, 2021 ). Moreover, data-mining of drug-related case reports from spontaneous reporting systems can provide us with a valuable source of information about the safety of specific drugs in real-life, especially for frail populations such as pregnant women ( Tkachenko et al, 2019 ; Carnovale et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review paper that included 705 cases of ICI-associated pericardial disease, the authors have stated that this condition is not as rare as initially believed but they have mentioned that there might be some biases coming from the fact that some malignancies complicate with pericardial effusion even in the absence of immunotherapy. Hence, the diagnosis of ICIs-related pericardial effusion is challenging ( 50 ).…”
Section: Mechanism Of Immune Cardiotoxicitymentioning
confidence: 99%
“…Another confounding factor that might alter the percentage of pericarditis is the use of radiation in conjunction with immunotherapy. It appears that radiation primes an endogenous antigen specific immune response ( 17 , 50 ). They expose potential shared antigens to T cell recognition, and this in turn might contribute to the development of pericarditis ( 30 ).…”
Section: Mechanism Of Immune Cardiotoxicitymentioning
confidence: 99%